Case Report: Based on the diamond theory, successful treatment of stubborn tibial nonunion after six surgeries using PRP-augmented therapy: a case report and literature review - Wang, Shiheng; Wu, Jiahua; Peng, Zhihao; Wang, Kunyu; Mo, Zhihong; Wu, Feng; Chen, Jianrong (Frontiers in Surgery, 2025)
BackgroundThe treatment of stubborn tibial nonunion remains a significant challenge. This case report describes a patient who underwent six surgeries and was treated using a stepwise surgical approach based on the diamond theory. The application of platelet-rich plasma (PRP) enhanced autologous iliac bone grafting combined with locked compression plate fixation ultimately achieved successful healing. This study also reviews relevant literature to explore the treatment experiences and outcomes of similar cases.Patient and methodsA middle-aged Asian male with severe heart disease underwent five failed surgeries, including two autologous bone graft procedures. Clinically, he presented with right calf pain, poor soft tissue condition on the anterior medial tibia, and signs of nonunion. During the sixth surgery, we applied a stepwise surgical procedure based on the diamond theory, achieving excellent clinical and bone healing, as well as satisfactory limb function at a follow-up of 11.3 months post-operation.ConclusionWe utilized a stepwise surgical procedure based on the diamond theory: locked compression plate internal fixation, PRP-enhanced structural autologous iliac bone grafting, and bioactive center creation techniques, providing a strong and stable mechanical and superior biological environment for the nonunion site.